2004
DOI: 10.4049/jimmunol.173.7.4470
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros Null Mice Display Defects in T Cell Selection and CD4 versus CD8 Lineage Decisions

Abstract: Previous evidence suggested that the hemopoietic-specific nuclear factor Ikaros regulates TCR signaling thresholds in mature T cells. In this study, we test the hypothesis that Ikaros also sets TCR signaling thresholds to regulate selection events and CD4 vs CD8 lineage determination in developing thymocytes. Ikaros null mice were crossed to three lines of TCR-transgenic mice, and positive selection, negative selection, and CD4 vs CD8 lineage decisions were analyzed. Mice expressing a polyclonal repertoire or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…We also observed inappropriate production of CD4SP cells in Rag1 Ϫ/Ϫ HYTCRtgGli3 ϩ/Ϫ thymus. Similar observation has been reported previously for Rag Ϫ/Ϫ HYTCRtg Ikaros null thymus (51). In the case of the Ikaros null thymus, the existence of CD4SP cells expressing a TCR interacting with MHC class I-presented ligand was attributed to reduced signal strength, whereas no reduction in apoptosis was observed.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We also observed inappropriate production of CD4SP cells in Rag1 Ϫ/Ϫ HYTCRtgGli3 ϩ/Ϫ thymus. Similar observation has been reported previously for Rag Ϫ/Ϫ HYTCRtg Ikaros null thymus (51). In the case of the Ikaros null thymus, the existence of CD4SP cells expressing a TCR interacting with MHC class I-presented ligand was attributed to reduced signal strength, whereas no reduction in apoptosis was observed.…”
Section: Discussionsupporting
confidence: 74%
“…The presence of CD4SP cells both in the thymus and the lymph nodes of Rag1 Ϫ/Ϫ HYTCRtgGli3 ϩ/Ϫ animals seemed surprising. Nevertheless, it has been previously shown that autoreactive CD4SP cells can be positively selected via MHC class I-restricted ␣␤TCR (51,52). This lineage diversion is attributed to decreased TCR signal strength.…”
Section: Hytcrtggli3mentioning
confidence: 99%
“…Autoreactive antibodies could be the result of defective negative selection (breakdown of central tolerance) or breakdown of peripheral B cell tolerance. In support of the former hypothesis, T cells in Ikaros-null mice do not undergo negative selection [27].…”
Section: Altered Lymphocyte Populations But No Leukemogenesis In Old mentioning
confidence: 71%
“…It has been hypothesized that Ikaros levels set signaling thresholds for activation in T cells [13,27,28]. It may play a similar role in B cells, since there are common pathways put into motion in B and T cells for regulation of proliferation in response to activation signals; these include the MAP kinase, PI-3 kinase and PLC-c pathways [29].…”
Section: Altered Lymphocyte Populations But No Leukemogenesis In Old mentioning
confidence: 99%
“…For B, E, and G, ( * ) P < 0.05; ( * * ) P < 0.01; ( * * * ) P < 0.001. Winandy 2004). In addition, Ikaros mutant strains contain a thymic CD4 SP population that exhibits immature characteristics, including low levels of TCR expression and the absence of maturation markers (Harker et al 2002;Naito et al 2007).…”
Section: Reduced Double-negative (Dn) Thymocytes In Ikzf1 δF4/δf4 Micementioning
confidence: 99%